Laser patterning of 2D-periodic go/rGO–structures by phase engineering - Thunholm, Malin Linnea (2017)
Femtosecond laser direct writing of reduced graphene oxide is a promising technique for micropatterning of electronical devices. The objective of this Final Year Project is to utilize femtosecond laser for making sub-micrometer periodic structures on the sample surface for graphene oxide. We conducted two-beam laser interference experiments with high power UV femtosecond laser and made parametric studies to investigate the photothermal effects from the photoreduction process. Samples were characterized by optical microscope and SEM. The results show that heat accumulation caused by high repetition rate and average power in the laser pulses highly affects the patterning.